Validation of a Proposal for a Children's Food Diary Proposal for Children with Eating Difficulties (Research, Society and Development, 2022)
Objective: To validate a proposal for a children's food diary. Methodology: This is an observational study of conceptual character and content validation, initiated by a systematic review of the literature, objectives and population. Results: The items and the proposal of the children's food diary were constructed, as well as the scale of content analysis of the evaluators of the area and lay people. The agreement for the proposal of the children's food diary established among professionals and among lay people was 80% CVI. Discussion: However, three questions did not reach the index, and must be reformulated, as they are considered of fundamental importance. Conclusion: The validation of a food diary proposal gathers information on food introduction and/or dietary difficulties, and establishes interdisciplinary communication among professionals.